2019
DOI: 10.7554/elife.46510
|View full text |Cite
|
Sign up to set email alerts
|

Tactile sensory channels over-ruled by frequency decoding system that utilizes spike pattern regardless of receptor type

Abstract: The established view is that vibrotactile stimuli evoke two qualitatively distinctive cutaneous sensations, flutter (frequencies < 60 Hz) and vibratory hum (frequencies > 60 Hz), subserved by two distinct receptor types (Meissner’s and Pacinian corpuscle, respectively), which may engage different neural processing pathways or channels and fulfil quite different biological roles. In psychological and physiological literature, those two systems have been labelled as Pacinian and non-Pacinian channels. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
10
28
0
Order By: Relevance
“…While the results in our first experiment, where we used electrical pulses to create bursting trains of the same periodicity but different number of spikes, were best explained by the burst gap code rather than a periodicity or rate code, the mean PSEs were lower than that would be predicted simply from the inter-burst duration. Though the difference in PSEs between electrical and mechanical stimulation was statistically significant, it is unknown whether this difference indicates any physiological importance, as it is well within the Weber fraction of~0.2-0.3 that has been previously reported in the literature [16,[34][35][36][37][38]. One possible explanation for this bias towards lower frequencies may be that electrical stimulation recruits all afferent types non-selectively, so that the slowly adapting (SA) afferents would be recruited in addition to the fast adapting (FA) afferents, whereas the mechanical stimulus predominantly activated FA afferents [5].…”
Section: Encoding Perceived Frequencysupporting
confidence: 66%
See 1 more Smart Citation
“…While the results in our first experiment, where we used electrical pulses to create bursting trains of the same periodicity but different number of spikes, were best explained by the burst gap code rather than a periodicity or rate code, the mean PSEs were lower than that would be predicted simply from the inter-burst duration. Though the difference in PSEs between electrical and mechanical stimulation was statistically significant, it is unknown whether this difference indicates any physiological importance, as it is well within the Weber fraction of~0.2-0.3 that has been previously reported in the literature [16,[34][35][36][37][38]. One possible explanation for this bias towards lower frequencies may be that electrical stimulation recruits all afferent types non-selectively, so that the slowly adapting (SA) afferents would be recruited in addition to the fast adapting (FA) afferents, whereas the mechanical stimulus predominantly activated FA afferents [5].…”
Section: Encoding Perceived Frequencysupporting
confidence: 66%
“…The discovery of the burst gap code for perceived frequency depended on the use of brief mechanical pulses that each only evoke a single spike in responding afferents, as had been verified using microneurography, allowing us to precisely control the spiking pattern of responding tactile afferents [5,16,17]. Electrical stimulation activates peripheral axons in a manner different than that of mechanical stimulation [18], by bypassing the specialised mechanoreceptors in the skin and directly stimulating the tactile afferent axons [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…If the NP h mid channel is not capable of spatial summation, it seems likely that the P channel is responsive to low-frequency vibrations at a low amplitude level (around the absolute threshold level). This would be an interesting complement to the study performed by Birznieks et al (2019).…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, Morioka & Griffin (2005) assumed that Vater-Pacini corpuscles might be involved at frequencies larger than 16 Hz. Finally, Birznieks et al (2019) found that the P channel is capable of causing a conscious perception following vibrations at a frequency as low as 6 Hz (fingertips). Although these studies only consider glabrous skin, we conclude that a similar behavior of these receptors/channels applies in hairy skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation